2004
DOI: 10.1007/s00424-004-1292-3
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent changes in potassium currents in guinea-pig coronary artery smooth muscle cells after acute cobalt loading in vivo

Abstract: The aim of the present study was to determine whether cobalt poisoning induces haem oxidase isoenzyme-1 (HO-1) in coronary artery smooth muscle, or accounts for any changes in coronary smooth muscle cell (SMCs) membrane ionic currents that could result from this type of heavy metal poisoning. In SMCs isolated from cobalt-treated guinea-pig coronaries, K+ channel currents (IK) were much smaller than those in cells isolated from non-treated animals. Haemin (HO substrate) increased IK concentration dependently. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…Our study unveils the modulatory role of the heme oxygenase system on the aldosterone-PLC signaling. Consistently, the suppression of the PLC-IP 3 pathway observed in the aorta of SHR and DOCA-salt rats in our study is in agreement with previous reports that showed the attenuation of PLC activity in isolated guinea pig coronary smooth muscle cells [29,30] in vitro. The simultaneous reduction of PLC activity, plasma aldosterone and NF-kB by an upregulated heme oxygenase system will attenuate tissue inflammation [44].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Our study unveils the modulatory role of the heme oxygenase system on the aldosterone-PLC signaling. Consistently, the suppression of the PLC-IP 3 pathway observed in the aorta of SHR and DOCA-salt rats in our study is in agreement with previous reports that showed the attenuation of PLC activity in isolated guinea pig coronary smooth muscle cells [29,30] in vitro. The simultaneous reduction of PLC activity, plasma aldosterone and NF-kB by an upregulated heme oxygenase system will attenuate tissue inflammation [44].…”
Section: Discussionsupporting
confidence: 95%
“…Similarly, the multifaceted interaction between the heme oxygenase system and the PLC-IP 3 secondary messenger system in hypertension is not fully understood. Although in-vitro studies have suggested an inhibitory role of hemin on PLC activity in isolated guinea pig coronary smooth muscle cells (SMCs) [29,30], no data at whole animal level are available to sustain the notion. Moreover, strain-specific and tissuespecific responses are common phenomenon in many observations; thus, it is unclear whether the administration of hemin to different models of hypertensive animals will evoke a similar response.…”
Section: Introductionmentioning
confidence: 96%
“…11,41 Consistently, the suppression of the PLC-IP 3 pathway observed in our study is in agreement with reports showing the attenuation of PLC activity in isolated guinea pig coronary smooth muscle cells in vitro. 46,47 The simultaneous reduction of PLC activity, ET-1 and NFkB by an upregulated HO system will attenuate tissue inflammation. 44,45,48 This notion is consistent with previous studies in which an upregulated HO system suppressed immune/inflammatory responses by abolishing macrophage infiltration and reducing mast-cell and basophils histamine release.…”
Section: Discussionmentioning
confidence: 99%